2017
DOI: 10.5301/ejo.5001005
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging in a Patient with Traumatic Choroidal Ruptures

Abstract: All patients presenting with blunt ocular trauma should undergo fundus examination to exclude damage to the optic nerve, retina, and choroid, and need close follow-up to avoid the development of secondary complications such as choroidal neovascularization. Optical coherence tomography angiography might add relevant information in the global evaluation and follow-up of choroidal ruptures in a noninvasive fashion, and could replace other invasive modalities such as FA or ICGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…However, there was no CNVM formation in this case. [ 16 ] In a report by Rezaei et al ., the authors demonstrated evolution and progression of vascular network patterns in the areas of posttraumatic CR suggestive of possible CNVM by OCT-based microangiography, although the lesion regressed over time without need of any anti-VEGF injection. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no CNVM formation in this case. [ 16 ] In a report by Rezaei et al ., the authors demonstrated evolution and progression of vascular network patterns in the areas of posttraumatic CR suggestive of possible CNVM by OCT-based microangiography, although the lesion regressed over time without need of any anti-VEGF injection. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a few case series describing the management of posttraumatic CR associated CNVM with anti-VEGF, the literature has very few isolated case reports demonstrating the use of OCTA in depicting the evolution of CR associated CNVM. [ 13 14 15 16 17 ] In the index report, we presented OCTA-guided the diagnosis of secondary CNVM following CR, where conventional FFA could not be performed and also showed its successful management with single injection of intravitreal ranibizumab.…”
Section: Discussionmentioning
confidence: 99%
“…They described a hypointense appearance in the choriocapillaris segmentation due to the lack of substance and the projection of the underlying choroidal vasculature as hyperintense flow. 7 Then, Preziosa et al described on MMI and OCTA a case of a 20-year-old woman with CR after an ocular blunt trauma who developed secondary CNV 6 months later and was treated by a single intravitreal injection of bevacizumab. Optical coherence tomography angiography showed the high-flow neovascularization and its contraction after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As AI technology continues to develop, doctors are also paying more attention to acquiring multimodal ocular imaging data, to provide a more comprehensive evaluation of ocular health. [42][43][44] By combining data from different imaging modalities, AI models can be trained to detect various diseases and conditions accurately. The use of multiple modal data in AI analysis suggests that more information from ophthalmic image models can play a vital role in analyzing systemic diseases.…”
Section: Slit Lamp Examinationmentioning
confidence: 99%